Aryl Hydrocarbon Receptor-Signaling Regulates Early Leishmania major-Induced Cytokine Expression - Münck, Niels-Arne; Roth, Johannes; Sunderkötter, Cord; Ehrchen, Jan (Frontiers in Immunology, 2019)
The early inflammatory skin micromilieu affects resistance in experimental infection with Leishmania major. We pursue the concept that macrophages, which take up parasites during early infection, exert decisive influence on the inflammatory micromilieu after infection. In order to analyze their distinctive potential, we identified differentially regulated genes of murine granuloma macrophages (GMΦ) from resistant and susceptible mice after their infection with metacyclic Leishmania major. We found induction of several cytokines in GMΦ from both strains and a stronger upregulation of the transcription factor aryl hydrocarbon receptor (AhR) in GMΦ from resistant mice. Using both an AhR agonist and antagonist we demonstrated that AhR is involved in Leishmania-induced production of TNF in macrophages. In vivo, single local injection of an AhR agonist in early lesions of susceptible mice caused an increased induction of Tnf and other cytokines in the skin. Importantly, local agonist treatment led to a reduction of disease severity, reduced parasite loads and a weaker Th2 response. Our results demonstrate that local activation of AhR has a beneficial effect in experimental leishmaniasis.